Meteorological observations at Syowa Station and Asuka Station in 1991 by the 32nd Japanese Antarctic Research Expedition - Toyoo Abe; Miyoki Iwamoto; Yoshitaka Sukegawa; Hiroshi Inayoshi; Masamichi Aono (National Institute of Polar Research, 1994)
This paper describes the results of meteorological observations carried out by the Meteorological Observation Team of the 32nd Japanese Antarctic Research Expedition (JARE-32) from 1 February 1991 to 31 January 1992 at Syowa Station, from 26 December 1990 to 1 December 1991 at Asuka Station and ozone observations from November to December 1990 on board the icebreaker SHIRASE. The observations, instruments and statistics at Syowa and Asuka Stations were the same as those of the JARE-31 observation team. In addition, at Syowa Station, ultraviolet-B radiation and other radiation observations were added for the Baseline Surface Radiation Network. At Asuka Station, aerological observations with 16 Omegasonde flights were carried out for the Antarctic Climate Research Program of the Meteorology and Glaciology group. The principal characteristics in the period of JARE-32 are as follows : 1) Blizzards at Syowa Station were encountered thirty-four times; the number of days of bizzards at Asuka Station was eighty-two. 2) At Syowa Station, the annual total sunshine duration was 1684.9 hours, which was the minimum record for the total period of observations. 3) The Antarctic ozone hole was observed for three successive years; the lowest value of daily total ozone amount was 159m atm-cm on 30 September, which was the second lowest value in the historical record. 4) On 23 May, a tower of snow smoke caused by hydraulic jump of katabatic wind was observed near Syowa Station.